UNODA Occasional Papers No. 35 - United Nations (United Nations, 2020)
This publication addresses the issue of military spending from various angles by examining the impact of military expenditures on security; the relationship between military spending and the achievement of the 2030 Agenda for Sustainable Development; the importance of gender perspectives in rethinking unconstrained military spending; and lessons learned from economic conversion movements. It has been published in support of the Sustainable Development Goals and the Secretary-General’s Agenda for Disarmament to encourage renewed research and analysis on the relationship between military spending and economic and social development.